PERAN ORGANISASI MAHASISWA DALAM PEMBENTUKAN SIKAP DEMOKRATIS - Dian Nastiti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Student organizations have a major role in forming the democratic attitudes of students. Building a democratic attitude requires training and practice in regular living. The college is one of the entities that prepares the next youth toward being democratic citizens. This study aims to describe the role of the Public Administration student organization in forming the democratic attitudes of its members through programs and barriers. The research approach is qualitative. Participants were selected using purposive sampling. Data was collected through observation, documentation, and interviews. Data validity was established through triangulation. The results of the study show that (1) the role of the Hima of Public Administration in forming democratic attitudes is as a campus partner, facilitator, and for its members; (2) the role of student organizations in forming democratic attitudes among students includes encouraging critical and disciplined thinking and responsibility; (3) barriers to improving democratic attitudes include limited human resources, financial constraints, and insufficient time management among members; and (4) efforts taken include designing attractive programs such as national dialogues, improving communication, establishing partnerships and coordination, and conducting evaluations.